Determinants in treatment decision-making in older patients with symptomatic severe aortic stenosis. Issue 1 (September 2015) - Boureau, A.S.; Trochu, J.N.; Colliard, C.; Volteau, C.; Jaafar, P.; Manigold, T.; Le Tourneau, T.; Berrut, G.; de Decker, L.
Highlights Little is known about how Heart Team treatment decisions among patients with aortic valve stenosis are made under routine conditions. The assessment of frailty is of paramount importance to guide patient-centred clinical decision-making in elderly patients with AVS. Comorbidities, functional status and physical performance, were significantly associated with the consensual treatment decision-making.